Local injection therapy with hyaluronic acid medical device in the case of shoulder joint impigment syndrome - E. I. Yaitskaya; D. V. disavic@mail.ru (Лечащий Врач)
The article presents the results of the study assessing the effectiveness of intra-articular administration of hyaluronic acid in patients with shoulder joint impigment syndrome. It was found that, medical device for the replacement of synovial fluid has a significant symptomatic effect, relieving or reducing pain, restores the completeness of movements in the joint and, thereby, improving functional performance.